Economics of Black Soldier Fly Production as a Farm Enterprise for Improved Household Income and Food Security - Mutuku, Kennedy Vaati (JOOUST, 2022)
Black Soldier Fly (BSF) farming is emerging as a new farm enterprise in Kenya poised to increase household income and food security of smallholder farmers. Consequently, commercialization of the enterprise requires farmers to know if the enterprise is economically viable. This study sought to assess the determinants of profitability and resource use efficiency of the BSF farm enterprise. The study employed a cross-sectional survey design where a census survey was conducted and 34 BSF farmers were interviewed. A double log-linear regression analysis on the determinants of profitability of the BSF farm enterprise was conducted. A linearized stochastic production function representing Cobb – Douglas production function was used in determining the resource use efficiency. Both models were statistically significant (p≤0.05) at a 5% level of significance. The results of the double log regression model revealed that 95.2% of the variation in the enterprise gross margin was explained by the independent variables [Substrate (X1), Labor(X2), Farm size(X3), household size (X4), the level of education(X5), age(X6), experience(X7), and gender(X8)]. Substrate and household size contributed positively and significantly to the enterprise gross margin. Labour was significantly and negatively correlated to the enterprise gross margin. Farm size, gender, level of education, and age of the farmer did not significantly influence the gross margin of the enterprise. Furthermore, the survey showed that a 1% increase in man-hours spent in the BSF farming enterprise would result in a 0.34% reduction in the gross margin while a 1% increase in the usage of the rearing substrate would lead to a 1.38% increase in the gross margin. The estimates of the Cobb Douglas production function revealed that 94.1% of the variation in the output from BSF enterprise can be explained by independent variables (Substrate, Labor, and Farm size) included in the model. Further, the substrate and labor were very significant in determining the BSF output while farm size was non-significant. The resource use efficiency indicators revealed that the Farmers were inefficient in utilizing the available resources. Labor was grossly and inefficiently over utilized while the substrate was underutilized. There is a need for farmers to reduce the man-hours spent in the BSF farms but at the same time increase significantly the utilization of more rearing substrate to improve their profitability. Furthermore, there is a need to empower women more by giving them access to property ownership or tailor made credit facilities and this will help in tilting the 70%/30% gender involvement in BSF farming. On this note, both National and County government incentives directed towards BSF farming, provision of credit facilities to women to enhance their participation, revitalization of extension services to enhance the utilization of farm labor (learning curve) for improved profitability are necessary. However, a long-term socio economic impact assessment on the BSF farming enterprise would be valuable to attract investors and interest in the insect production sector for animal feed. On the same note, further research can be undertaken on the effect of BSF farming on improved livelihood moderated by government incentives.
Keywords: Eggies; Farm Enterprise